Food Entrainment, Arousal, and Motivation in the Neonatal Rabbit Pup - Caba, Mario; Lehman, Michael N.; Caba-Flores, Mario Daniel (Frontiers in Neuroscience, 2021)
In the newborn rabbit, the light entrainable circadian system is immature and once a day nursing provides the primary timing cue for entrainment. In advance of the mother’s arrival, pups display food anticipatory activity, and metabolic and physiological parameters are synchronized to this daily event. Central structures in the brain are also entrained as indicated by expression of Fos and Per1 proteins, GFAP, a glial marker, and cytochrome oxidase activity. Under fasting conditions, several of these rhythmic parameters persist in the periphery and brain, including rhythms in the olfactory bulb. Here we provide an overview of these physiological and neurobiological changes and focus on three issues, just beginning to be examined in the rabbit. First, we review evidence supporting roles for the organum vasculosum of lamina terminalis and median preoptic nucleus in homeostasis of fluid ingestion and the neural basis of arousal, the latter which also includes the role of the orexigenic system. Second, since FAA in association with the daily visit of the mother is an example of conditioned learning, we review evidence for changes in the corticolimbic system and identified nuclei in the amygdala and extended amygdala as part of the neural substrate responsible for FAA. Third, we review recent evidence supporting the role of oxytocinergic cells of the paraventricular hypothalamic nucleus as a link to the autonomic system that underlies physiological events, which occur in preparation for the upcoming next daily meal. We conclude that the rabbit model has contributed to an overall understanding of food entrainment.